2017
DOI: 10.1016/j.bbrc.2016.09.088
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pathways driving early synaptic pathology in Alzheimer's disease

Abstract: The current state of the AD research field is highly dynamic is some respects, while seemingly stagnant in others. Regarding the former, our current lack of understanding of initiating disease mechanisms, the absence of effective treatment options, and the looming escalation of AD patients is energizing new research directions including a much-needed re-focusing on early pathogenic mechanisms, validating novel targets, and investigating relevant biomarkers, among other exciting new efforts to curb disease prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 172 publications
1
60
0
Order By: Relevance
“…These results consistent with reports that dantrolene exerted beneficial effects in several AD mouse models [6466] and suggested that blocking RyanR is a viable therapeutic strategy. This idea is reviewed in depth by Dr. Grace Stutzmann and her colleagues in the accompanying review article [71]. …”
Section: Ryanodine Receptors In Admentioning
confidence: 99%
“…These results consistent with reports that dantrolene exerted beneficial effects in several AD mouse models [6466] and suggested that blocking RyanR is a viable therapeutic strategy. This idea is reviewed in depth by Dr. Grace Stutzmann and her colleagues in the accompanying review article [71]. …”
Section: Ryanodine Receptors In Admentioning
confidence: 99%
“…Our findings suggest that both Aβ 42  PUMA might separately or jointly damage  m . Taken together, these data indicate that Neuronal calcium (Ca 2+ ) dyshomeostasis has been proposed to play a crucial role in AD disease progression [68]. However, the mechanisms of Ca 2+ dysregulation are not clear.…”
Section: Discussionmentioning
confidence: 98%
“…[88][89][90] How reductions in voltage-dependent calcium channel function may further increase AD+P risk is not known, however, impairments of intracellular Ca 2+ homeostasis are present in AD, and can contribute to synaptic dysfunction and cognitive impairments. 91 We recently estimated the annual incidence of psychosis in AD at 10%. 40 Thus there is an opportunity to intervene prior to psychosis onset if individual predictors can be identified.…”
Section: Discussionmentioning
confidence: 99%